2023
DOI: 10.1021/acs.macromol.2c02054
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Polyester Upcycling for Diversifying a Problematic Waste Stream

Abstract: We are facing a rapidly growing plastic pollution crisis, which is adversely affecting communities and ecosystems across the globe. Polymer scientists have an urgent obligation to develop and implement strategies for reutilizing plastic waste streams instead of continually relying on virgin feedstocks in plastic manufacturing. Postconsumer and postindustrial plastic items should be treated as valuable resources instead of discarding them. In order to do this, technological outlets must be developed to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 143 publications
1
13
0
Order By: Relevance
“…PET is extensively used in packaging and textiles, while BPA-PC finds applications in electronic, constructional, and optical applications. For PET, several typical depolymerization methods, including alcoholysis, glycolysis, aminolysis, and hydrolysis, were well reviewed. ,, In our work, the methanolysis of PET required a higher temperature (Table ) compared with PLA. For example, PLA could be fully depolymerized at 140 °C by methanolysis.…”
mentioning
confidence: 79%
“…PET is extensively used in packaging and textiles, while BPA-PC finds applications in electronic, constructional, and optical applications. For PET, several typical depolymerization methods, including alcoholysis, glycolysis, aminolysis, and hydrolysis, were well reviewed. ,, In our work, the methanolysis of PET required a higher temperature (Table ) compared with PLA. For example, PLA could be fully depolymerized at 140 °C by methanolysis.…”
mentioning
confidence: 79%
“…Chemical upcycling primarily involves the conversion of plastic polymers into their monomers or some short chains which can therefore be used as fuels or feedstock for polymerization reactions and the further production of VAP. , As a result, plastic waste can be converted into solid carbonaceous materials, liquids including acids and fuels, and gaseous fuels such as hydrogen and syngas. The separation of various plastics, contamination, the potential creation of corrosive gases, and the typical low selectivities of products are some of the practical issues that currently plague chemical upcycling operations. , Although conventional chemical upcycling uses more energy, it is a promising strategy since it may produce a wide range of readily available compounds with the judicious development of catalysts and reaction conditions. Further, biological upcycling mainly focuses on microorganisms and enzymatic activity for the valorization of plastics with some review articles published. Ru et al revealed that the enzymatic reactions are inefficient after reviewing the microbial valorization of plastic waste . The expense of utilizing or maintaining enzymes and bacteria, the constrained variety of reaction conditions, and the narrow scope to mostly condensation polymers are further issues with biological techniques for upcycling plastics …”
Section: Conventional Methods Of Plastic Waste Managementmentioning
confidence: 99%
“…Poly­(ethylene terephthalate) (PET) is the most important aromatic polyester available today, widely used in film and beverage packaging and textiles. , However, the fossil-based nature of terephthalic acid (TPA) or its dimethyl ester (dimethyl terephthalate) used in PET production has raised serious questions concerning its sustainability. Consequently, there has been an enormous interest recently in the industry and academia to develop alternative biobased aromatic dicarboxylic acids and dicarboxylates as a potential substitute for TPA in aromatic polyesters. One significant achievement in this direction is the development of 2,5-furandicarboxylic acid (FDCA) derived from a sugar-based building block. The polycondensation of FDCA with ethylene glycol yields a 100% biobased polyester known as poly­(ethylene 2,5-furandicarboxylate), or PEF, which possesses comparable or even slightly better properties than PET. , Inspired by this successful example, several alternative biobased aromatic diacid or dicarboxylates have been reported for polyester synthesis, particularly using the phenolic and furanic building blocks obtained from lignocellulosic biomass. …”
Section: Introductionmentioning
confidence: 99%